C/N Vacancy Co‐Enhanced Visible‐Light‐Driven Hydrogen Evolution of g‐C3N4 Nanosheets Through Controlled He+ Ion Irradiation. Issue 4 (7th January 2019) - Wang, Xuening; Wu, Liang; Wang, Zhaowu; Wu, Hengyi; Zhou, Xuemei; Ma, Hongyu; Zhong, Huizhou; Xing, Zhuo; Cai, Guangxu; Jiang, Changzhong; Ren, Feng
Abstract : Graphitic carbon nitride (g‐C3 N4 ) is reported to be a promising metal‐free semiconductor for photocatalytic water splitting. However, the performance of g‐C3 N4 is substantially limited by its insufficient visible‐light absorption and low photogenerated charge carrier separation efficiency. In this work, an innovative method (ion irradiation) to efficiently introduce both defined C‐ and N‐vacancies ( V C and V N ) simultaneously into g‐C3 N4 nanosheets are explored. Unlike traditional chemical methods, by controlling He + ion fluence, tunable vacancy concentrations are able to be obtained in g‐C3 N4 . Defect‐engineered g‐C3 N4 shows highly improved performance under optimized conditions, the defective g‐C3 N4 exhibits a significantly higher (2.7‐fold) hydrogen evolution rate of 1271 µmol g −1  h −1 than that of the g‐C3 N4 nanosheets under visible light ( λ  > 420 nm) illumination. Meanwhile, the defective g‐C3 N4 exhibits a significantly enhanced (threefold) photocurrent density as photoanodes for photoelectrochemical (PEC) water splitting. Further characterizations show that the enhanced visible light absorption and an extended charge carrier lifetime, can be ascribed to the presence of C‐ and N‐ vacancies. These experimental results are in line with density functional theory (DFT) calculations. Therefore, the present work shows that defect‐engineering on g‐C3 N4 using ion irradiation technique, is an effective, controllable, and defined approach to improve the photocatalytic and PEC water splitting performance of g‐C3 N4 . Abstract : Defective g‐C3 N4 photocatalysts are successfully prepared by ion irradiation technology, achieving simultaneous introduction of C– and N– vacancies and the control of vacancy concentration. The C– and N– vacancies help to enhance the absorption of visible light and the separation efficiency of photogenerated carriers, respectively, thus realizing the remarkable improvement of photocatalytic hydrogen production performance.